Pencarian Berita Berbahasa Indonesia Menggunakan Metode BM25 - Khalisma Frinta; Indriati Indriati; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Rapid technological developments have resulted in increased use of the internet as a source of online information providers from around the world. Users use a search engine for searching information. These developments also make digital document storage increase. News is a source of information about an event or opinion that has important and interesting value to be widely publicized through the mass media. The unlimited reach of readers and the efficiency of time makes the various media reports turn to online media. Information retrieval aims to produce documents that are relevant to the needs of users of a collection of information automatically based on keywords in the queries given by users. The application of information retrieval is expected to facilitate information retrieval and obtain accurate results. BM25 is a system in the ranking process that is used to sort the results of a match (similarity) to all training documents based on the query. The BM25 method is categorized as the best method in the best match class. Tests are based on precision @k values ​​and r-precision values ​​for 12 queries. The best test results for precision @k values ​​when k=5, which is 0.83. While the best results for r-precision values ​​are 1.